OVERCOMING PSYCHOLOGICAL BIAS AMONG STOCK INVESTORS: SEMINAR FOR A STOCK INVESTOR COMMUNITY - Dananjaya, Yanuar; Siahaya, Janice Carysa (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This community service was a webinar for stock investors conducted in collaboration with Zhuan Community, a community of Indonesian stock investors. One of the problems usually faced by stock investors is psychological bias in making investment decisions. Some papers have reported that Indonesian stock investors are prone to psychological bias. In this webinar, it was shown to participants that humans are affected by psychological factors during decision making, especially financial related decisions. Those psychological factors create behavioral bias that reduce investment performance. Several examples of behavioral biases common in stock investors are introduced, namely overconfidence bias, herding behavior, disposition bias, and sentiment bias. Steps to mitigate the biases are offered. It is expected that understanding of how psychological factors affect investors behavior will enable participants to reduce its effect and thus act more rationally in making investment decisions.